2004
DOI: 10.1016/j.watres.2003.09.040
|View full text |Cite
|
Sign up to set email alerts
|

Validating sample preservation techniques and holding times for the approved compliance monitoring methods for haloacetic acids under the US EPA's stage 1 D/DBP rule

Abstract: Haloacetic acids (HAAs), which are formed during the disinfection of drinking waters with chlorine, are regulated by the US Environmental Protection Agency (EPA) under the Stage 1 Disinfectant/Disinfection Byproducts (D/DBP) Rule. Recently, three studies have been reported indicating that low concentrations of HAAs can also be formed during disinfection with chloramines. Methods currently approved for compliance monitoring under the Stage 1 Rule arrest the chlorine-mediated formation of HAAs by adding ammonium… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
8
0
1

Year Published

2005
2005
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 5 publications
(11 reference statements)
0
8
0
1
Order By: Relevance
“…For the analysis of drinking water samples, supplementary recovery tests may be necessary to be conducted because, chlorinated water includes residual chlorine that could affect the extraction recovery of analytes. Under these conditions, sodium thiosulfate must be added to reduce residual chlorine in chlorinated water samples (Pepich et al, 2004). Indeed, it…”
Section: Matrix Effectmentioning
confidence: 99%
“…For the analysis of drinking water samples, supplementary recovery tests may be necessary to be conducted because, chlorinated water includes residual chlorine that could affect the extraction recovery of analytes. Under these conditions, sodium thiosulfate must be added to reduce residual chlorine in chlorinated water samples (Pepich et al, 2004). Indeed, it…”
Section: Matrix Effectmentioning
confidence: 99%
“…Formation of haloacetic acids can occur during the preservation and storage of drinking water. Pepich et al (2004) added ammonium chloride to quench the freeavailable chlorine in treated surface water and found it to prevent most of the haloacetic acid formation after 28 d of storage. The observed increase in haloacetic acids occurred mostly over the first two days, and was mainly dichloroacetic acids.…”
Section: Microbiology and Disinfection Chemistrymentioning
confidence: 99%
“…The study also showed that the use of NH 4 Cl as a quenching agent in chloramination kinetic experiments conducted with preformed chloramine resulted in false high HAA concentrations at early reaction times. Although it was previously reported that NH 4 Cl was able to preserve formed HAA during sample storage time, a close examination of the data indicated continued formation of dichloroacetic acid (DCAA) after NH 4 Cl addition, with the DCAA concentration increasing from 3.8 to 7.7 μg/L after 28 days of storage time (Pepich et al, 2004). Other researchers observed an increase of 20% for DCAA concentration after 14 days of storage time in utility samples quenched by NH 4 Cl (Krasner et al, 1989).…”
mentioning
confidence: 95%
“…The quenching agents that can be used for chlorinated water samples include ammonium chloride (NH 4 Cl), reducing agents such as salts of sulfite or thiosulfate, and ascorbic acid. NH 4 Cl showed the ability to preserve spiked haloacetic acid (HAA) concentrations in water samples during a sample holding time of two weeks (Krasner et al, 1989), and it provides the advantage of controlling microbial growth in chlorinated samples (Pepich et al, 2004). Suppression of microbial activity in HAA samples is important because some HAA species have been shown to undergo microbial degradation (Baribeau et al, 2005; McRae et al, 2004).…”
mentioning
confidence: 99%
See 1 more Smart Citation